Optimization of Waste Management on The Basis of Research in the 'PIKRES' Manufacturing Company - Marcin KŁAK (Communications of International Proceedings, 2023)
The purpose of this article is to present waste management issues and attempts to optimize waste management at the PIKRES manufacturing company. In order to achieve this goal, data were used from the company's documents covering the scope of waste records and from information obtained during an in-depth interview. In addition, the authors reviewed the literature on the topic under consideration. Waste was presented in theoretical terms, along with legal aspects of waste management. In particular, the organization of waste management is described. The main part of the article is devoted to own research on the process of modernization of waste management in a selected company. The profile of the selected company is presented, the identification of the waste generated and the proposal for modernization of waste management are indicated. In the last part of the study, corrective measures of optimization nature and final conclusions are detailed.
Keywords: waste; waste management; optimization; manufacturing company